Behavioural fever in zebrafish larvae. (February 2017) - Rey, Sonia; Moiche, Visila; Boltaña, Sebastian; Teles, Mariana; MacKenzie, Simon
Abstract: Behavioural fever has been reported in different species of mobile ectotherms including the zebrafish, Danio rerio, in response to exogenous pyrogens. In this study we report, to our knowledge for the first time, upon the ontogenic onset of behavioural fever in zebrafish ( Danio rerio ) larvae. For this, zebrafish larvae (from first feeding to juveniles) were placed in a continuous thermal gradient providing the opportunity to select their preferred temperature. The novel thermal preference aquarium was based upon a continuous vertical column system and allows for non-invasive observation of larvae vertical distribution under isothermal (TR at 28 °C) and thermal gradient conditions (TCH : 28-32 °C). Larval thermal preference was assessed under both conditions with or without an immersion challenge, in order to detect the onset of the behavioural fever response. Our results defined the onset of the dsRNA induced behavioural fever at 18–20 days post fertilization (dpf). Significant differences were observed in dsRNA challenged larvae, which prefer higher temperatures (1–4 °C increase) throughout the experimental period as compared to non-challenged larvae. In parallel we measured the abundance of antiviral transcripts; viperin, gig2, irf7, trim25 and Mxb mRNAs in dsRNA challenged larvae under both thermal regimes: TR and TCh . Significant increases in the abundance of all measured transcripts were recorded under thermal choice conditions signifying that thermo-coupling and the resultant enhancement of the immune response to dsRNA challenge occurs from 18 dpf onwards in the zebrafish. The results are of importance as they identify a key developmental stage where the neuro-immune interface matures in the zebrafish likely providing increased resistance to viral infection. Highlights: Behavioural fever is a synergic immune response to infection in ectotherms. Zebrafish larvae ( Danio rerio ) select their preferred temperature within a vertical gradient tank. The onset of the behavioural fever response was established at 18–20 dpf. When challenged with dsRNA zebrafish larvae display behavioural fever coupled to an increased antiviral mRNA response.